The Effects of Sampling Depth on Benthic Testate Amoeba Assemblages in Freshwater Lakes: A Case Study in Lake Valdayskoe (the East European Plain) - Vlad V. Sysoev; Andrey N. Tsyganov; Fedor Y. Reshetnikov; Yuri A. Mazei (Diversity, 2022)
Testate amoebae are widely used as proxies in paleoecological reconstructions of lacustrine environments; however, our knowledge on their distribution along depth gradients are limited. This study investigates the distribution of benthic testate amoebae along a sampling depth gradient (0 to 57 m) and related environmental characteristics in Lake Valdayskoe, Russia. In total, 101 species belonging to twenty-one genera were identified. Four types of testate amoeba assemblages (littoral, sublittoral, bottom slope and profundal) were distinguished that corresponded well to the bottom zones of the lake. The results of redundancy analysis indicated that sampling depth, temperature, pH and bottom inclination significantly explained 40.2% of the total variance in the species composition. Temperature and sampling depth had the largest individual contributions of 19.2 and 7.4% (p < 0.001), respectively. The minimal values of species diversity were observed on the littoral and at the lower boundary of the thermocline. We estimated depth optima and ranges for the species with high occurrences and distinguish stenobathic and eurybathic species. These data might improve the interpretations of paleoecological records of subfossil testate amoeba assemblages in lacustrine surface sediments and serve as basis for the development of a transfer function for reconstruction of lake depths.